86 PARTIAL PURIFICATION AND CHARACTERIZATION OF A MITOCHONDRIAL EXONUCLEASE. (1st January 2005) - Hassan, S.; Low, R.
Abstract : Mitochondria have been shown to contain a potent DNA endonuclease (endonuclease G) in their intermembrane space (1). Endonuclease G is Mg2+-dependant, inhibited by high salt concentrations and is released during apoptosis to help degrade nuclear DNA (2). While studying this endonuclease our lab also noticed exonuclease activity in our preparations. This exonuclease activity has similar properties to endonuclease G It is Mg2+-dependant, inhibited by salt but is more active in a lower pH than endonuclease G. It has been partially purified and is currently being analyzed by Maldi-Tof mass spectrometry. Supported in part by the NIH Short Term Training Grant 5 T35 DK07496-19